Optical properties of deposit of red blood cells suspended in dextran solutions - Strzelecka, Joanna; Bosek, Maciej; Grzegorzewski, Bronisław (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
The optical properties of the deposit of red blood cells (RBCs) formed during sedimentation have been investigated. The human blood was obtained from healthy donors. RBCs were suspended in isotonic saline containing Dextran 70 of concentrations 2, 4 and 6 g/dl. Hematocrit of the samples was adjusted to 40%. The intensity of the light scattered by the samples of the RBC suspensions as a function of time and altitude from the bottom of a sample was measured. The region occupied by forming and sedimenting aggregates and the region occupied by deposit of the cells can be found in the sample and the temporal dependence of position of the interface separating both regions, called the deposit formation curve, can be determined. This curve exhibits the growth phase and the packing phase. We have obtained the mean intensity of light scattered by the deposit as a function of time. This intensity exhibits a monotonous decay with time over the growth as well as the packing phase, what shows that packing of the deposit occurs in the same way in both phases. The dependence from time of the mean hematocrit of the deposit was determined. We have introduced an empirical expression describing this dependence. Finally, using this dependence, we have obtained the mean intensity of light scattered by the deposit as a function of hematocrit. We have shown that this intensity follows an exponential decay. The values of an optical parameter of the deposit were found from this dependence.
Optica Applicata, Vol. 40, 2010, nr 1, s. 177-185
Keywords: optyka; light scattering; RBC sedimentation; dextran